Development of Realistic Based Interactive Media to Improve Class IV Elementary School Learning Outcomes - Silvia, Nova; Biran, Megaiswari; Ahmad, Syafri; Zainil, Melva (Jurnal Penelitian Pendidikan IPA, 2024)
The learning process is a communication process and takes place in a system between interactive media and learning tools. This research was carried out with a 4-D approach.The products developed were validated by experts and then tested on grade IV elementary school students. Of the four validators who had conducted the assessment, an average of 86% was obtained with a very valid category. There are nine aspects assessed, namely aspects of accuracy, completeness, interest, providing learning opportunities, providing assistance for learning, motivational quality, learning flexibility, social quality of instructional interactions, can have an impact on students, and can have an impact on teachers and their learning. The results of the practicality test by grade IV teachers of SD IT Nurul Ikhlas, SD Islam Al-Azhar 32, and SD IT Buah Hati showed that the interactive media based on RME that had been developed obtained very practical results with a practicality percentage of 92%. The results of the practicality test by grade IV students of SD IT Nurul Ikhlas, SD Islam Al-Azhar 32, and SD IT Buah Hati showed that the interactive media based on RME in mathematics learning that had been developed had a practicality percentage of 91% and was included in the very practical category. The results of the effectiveness test by grade IV students of SD IT Nurul Ikhlas, SD Islam Al-Azhar 32, and SD IT Buah Hati showed that the interactive media based on RME that had been developed was effective in use with an average value of 0.74 with an effective category using the N-gain percentage. The Development of Interactive Media Based on Realistic for Grade IV Elementary Schools is a valid, practical and effective learning media